2010
DOI: 10.1007/978-3-211-99370-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Discogenic Low Back Pain with Intradiscal Electrothermal Therapy (IDET): 24 Months Follow-Up in 50 Consecutive Patients

Abstract: The findings of this study suggest that durable clinical improvements can be realized after IDET in highly selected patients with mild disc degeneration, confirmatory imaging evidence of annular disruption and concordant pain provocation by low pressure discography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In some cohort studies, intradiscal electrothermal therapy was reported to have success rates as high as 75% 7980. The mechanism of action was believed to be a sort of thermal annealing of AF damage as well as thermal disruption of nerve fibers.…”
Section: Implication For Treatmentsmentioning
confidence: 99%
“…In some cohort studies, intradiscal electrothermal therapy was reported to have success rates as high as 75% 7980. The mechanism of action was believed to be a sort of thermal annealing of AF damage as well as thermal disruption of nerve fibers.…”
Section: Implication For Treatmentsmentioning
confidence: 99%
“…The goal of all these techniques is to close the gap between failed conservative treatment and open surgery, especially for contained herniated discs. 16 27 …”
Section: Introductionmentioning
confidence: 99%
“…Several minimally invasive methods have been proposed for the management of pain 9, 10. Intradiscal electrothermal therapy involves ablation of the nociceptive receptors in the ligaments and annulus fibrosus by heat 11, 12; however, with the complete elimination of pain, the removal of the pain receptors also results in the loss of the indicator role of pain. Disc protrusion caused by uncontrolled mechanical loading by the patient can lead to nerve damage or function loss at the innervated field by increasing the pressure in the nucleus pulposus 13.…”
Section: Introductionmentioning
confidence: 99%